The Prohibition of Perfidy in International Humanitarian Law - المالكي, هادي نعيم; خضير, عمر عباس (Journal of Legal Sciences, 2021)
This research id entitled "The Prohibition of Perfidy in International Humanitarian Law".  International humanitarian law includes some international agreements that aim to regulate hostilities, and the use of tools and means of warfare (The Hague Law), Where there are many international rules that govern the conduct and management of hostilities, there are some provisions that limit the use of certain means and methods during armed conflict, Whether by prohibiting the use of specific methods of fighting, or prohibiting or restricting the use of certain types of weapons, The dedication of these rules to the law of armed conflict comes in implementation of the principle of the law of war, which restricts the authority of the parties to the conflict to choose the means to harm the enemy.The issue of regulating the limitation of the resort to treachery is an important topic. If international humanitarian law came for the purpose of humanitarian protection in the first place, it must limit the right of parties to armed conflict by prohibiting the use of means and methods that leave effects outside the framework of humanity, that is, in other words to be the provisions of this law are of a preventive nature aimed at protecting the human being and avoiding the risks of hostilities that cannot be managed and remedied if they happen.